Genetic alterations in peritoneal metastatic tumors predicted the outcomes for hyperthermic intraperitoneal chemotherapy - Nguyen, Quynh-Anh; Chou, Wan-Hsuan; Hsieh, Mao-Chih; Chang, Che-Mai; Luo, Wei-Tzu; Tai, Yu-Ting; Chang, Wei-Chiao (Frontiers in Oncology, 2023)
Introduction Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) are considered for patients with peritoneal metastasis (PM). However, patients selection that relies on conventional prognostic factors is not yet optimal. In this study, we performed whole exome sequencing (WES) to establish tumor molecular characteristics and expect to identify prognosis profiles for PM management. Methods In this study, blood and tumor samples were collected from patients with PM before HIPEC. Tumor molecular signatures were determined using WES. Patient cohort was divided into responders and non-responders according to 12-month progression-free survival (PFS). Genomic characteristics between the two cohorts were compared to study potential targets. Results In total, 15 patients with PM were enrolled in this study. Driver genes and enriched pathways were identified from WES results. AGAP5 mutation was found in all responders. This mutation was significantly associated with better OS (p = 0.00652). Conclusions We identified prognostic markers that might be useful to facilitate decision-making before CRS/HIPEC.